Challenges and Pitfalls for Implementing Digital Health Solutions in Clinical Studies in Europe - Meyerheim, Marcel; Burns-Gebhart, Anna; Mirzaie, Kasra; Garani-Papadatos, Tina; Braun, Yvonne; Graf, Norbert (Frontiers in Digital Health, 2021)
The increasing number of digital solutions developed for use in clinical health care settings is accompanied by new challenges to develop and conduct clinical studies that include eHealth technologies. Clinical study implementation plans often disregard or underestimate the necessity of additional administrative and logistic tasks required at clinical sites as well as ethical aspects to test digital solutions. Experiences made in the run-up of an observational clinical feasibility study at three international clinical sites in the framework of the MyPal project (https://mypal-project.eu/) result in recommendations to avoid delays and barriers in the planning of such prospective studies in clinical and also palliative care for increased efficiency.